Meningkatkan Kemampuan Berpikir Kritis Siswa melalui Model Contextual Teaching And Learning: Quasi-Eksperimen - Siti Meila Rahmawati; Nani Sutarni; Rasto Rasto; Ilham Muhammad (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to examine the effect of using contextual teaching and learning models on students' critical thinking skills. In this study, two classes of class X students at SMAN 1 Ciracap for the 2022/2023 academic year were selected as the experimental group that applied the CTL model, while the other classes became the control group that used the conventional model. Data was collected through pretest and posttest, and analyzed using descriptive and inferential statistical methods. The results showed that students in the experimental group achieved higher scores compared to the control group, with an average N-Gain of 5.76 indicating a high increase in critical thinking skills. In addition, the significance value of the data is 0.000, which indicates a significant influence from the application of contextual teaching and learning models. In conclusion, it can be concluded that the model has a significant influence on students' critical thinking skills.